The NAIRU-concept: A few remarks - Karl Pichelmann; Ulrich Schuh (Institute for Advanced Studies (IHS), 1996)
This note gives a brief survey of main theoretical and empirical issues with respect to the NAIRU concept. According to modern labour market literature NAIRU is defined as the rate of unemployment at which inflation stabilizes in the absence of any wage-price surprises. Conventional thinking about the equilibrium unemployment rate assumes that in the long run NAIRU is determined solely by supply side factors of the labour market. We show that quite complex adjustment dynamics may arise even in simple log-linear wage-price models. Furthermore we provide a survey on a number of hysteresis-mechanisms which could lead to permanent shifts of equilibrium unemployment over time, implying that an unique long run NAIRU may not even exist. In addition to theoretical issues we refer to two serious problems which might arise with empirical applications of the NAIRU concept. First various empirical studies suggest that results highly depend on model specifications. Second a considerable amount of statistical imprecision is inherent in the results obtained from empirical estimates. For these reasons, we argue, that policy conclusions drawn from the NAIRU concept must be judged with utmost care, particularly since in many countries a number of labour market measures as well as monetary policy are based on this concept.
Keywords: E24; C51; 330; NAIRU; hysteresis mechanisms; Phillips-Kurve; Arbeitslosigkeit; Lohn; Hysteresis; Theorie